The Study of Monday Effect in the Stock Exchange of Thailand - Jenwittayaroje, Nattawut (NIDA Business Journal, 2023)
This study examines the Monday Effect phenomenon (the fact that the averaged return on Monday is lower than those on the other days of a week) in SET index, SET50 index, sSET index and MAI index of the Stock Exchange of Thailand (SET) during 1975-2019. The results show that, for SET index, the Monday’s averaged return is negative, the lowest compared with the other days’ averaged returns, and is about -0.126% per day or about 0.200% statistically significantly lower than the other days’ averaged returns. The results remain qualitatively unchanged, using either price returns or total returns in the analysis. The Monday Effect can be found in every stock index, except the sSET index. Moreover, the results do not find the higher risk (measured by standard deviation of returns) on Monday returns than on the other days’ returns. Therefore, the results of this study reject the efficiency of Thai stock market, and lead to the trading strategies that can generate abnormal returns. Finally, the empirical evidence of Monday Effect in Thai stock market is consistent with those in other stock markets.